Automated gas extraction system for the handling of radioactive waste gases from routine carbon-11 production. (6th August 2018) - Shadwell, Matthew; Paneras, Nikolas; Izard, Mike; Hoffmann, Emmy; Perkins, Gary
Abstract: Radiopharmaceutical production processes have the ability to produce radioactive waste in both liquid and gases forms. Control of radioactive waste gas emissions continues to be a significant issue for radiochemistry laboratories. As these facilities are often situated within urban areas emissions must be controlled to ensure the public's safety. Various methods have been employed but most of these methods use a passive gas capture bag which is often located within the hotcell where the work is being conducted. Here we report on an active system that completely removes the waste gas from the hotcell and stores the gases for decay in a safe location. This system is not only cost effective but helps to protect the operators from dose that they would otherwise receive due to working around the radioactive waste gas bag. This gas extraction system is now in continuous use and forms an integral part of the carbon-11 production process at National Research Cyclotron Facility.